Kedudukan Orang Tua Angkat Terkait Wali Anak Dibawah Umur Sebagai Penghadap Dalam Akta Notaris - Astari, Made Sintya Wahyu Wulan; Astariyani, Ni Luh Gede (Acta Comitas, 2025)
The aim of preparing this article is to explore the current legal provisions in Indonesia regarding the guardianship of minors and the status of adoptive parents as guardians of minors when appearing before a notary to make a deed. The discussion of the problem in this article uses a normative juridical research method that combines a statutory regulatory approach with a conceptual approach. Based on the findings of this research, provisions regarding child guardians exist on a number of different legal bases. Firstly, the marriage law regulates this through Articles 50 to Article 54. Furthermore, this regulation is also contained in the Civil Code which includes it in Articles 331, 351 and 361. Lastly, regulations regarding child guardians are also regulated in the child protection law, especially in Articles 33 and 34. The position of adoptive parents as guardians in legal actions carried out by orphaned minors as persons in notarial deeds can be said to be equal to biological parents because of their responsibility. and the obligations entrusted to guardians, similar to those carried out by real parents, must be carried out by caring for and caring for minor children under their supervision, and all assets owned by the child must be managed and utilized optimally..